ANALISIS PELAKSANAAN PENDIDIKAN KARAKTER MANDIRI PESERTA DIDIK OLEH GURU MATA PELAJARAN SOSIOLOGI KELAS XI F SMAN 10 PONTIANAK - Maudy Meilinda Iasya (Jurnal Pendidikan Edukasi Kusuma Bangsa, 2025)
This study aims to analyze the implementation of independent character education of students by teachers of Sociology class XI F SMAN 10 Pontianak. Independent character education is an effort to form students who are able to be responsible, confident, and take initiative in the learning process. The method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The data sources in this study consisted of a sociology teacher who taught in class XI F, namely Mrs. DP and four students who were the subjects of the study, namely EWF, RPIW, ADB, and TW. Data collection was carried out through direct observation in the classroom, interviews with teachers and students, and analysis of the results of the implementation of independent character education for students by teachers of sociology subjects class. The results of the study show that teachers have prepared plans through teaching modules that contain independent character values. The implementation of learning is carried out by providing space for students to choose learning methods and complete assignments independently, most of the students showed the development of independent characters such as initiative, confidence, and responsibility. Teachers provide challenges gradually, relate learning to real life, and give appreciation for the learning process. Overall, the implementation of independent character education in grade XI F is going quite well, although continuous support is still needed from teachers, schools, and the surrounding environment to strengthen the overall character formation of students.